Seed nutritional quality comparison of vegetable soybean genotypes at fresh pod and mature stage - B. Tian, Q. Zhang, X. Liu, C. Liu, Y. Li, B. Tu, X. Wang (Emirates Journal of Food and Agriculture, 2019)
Vegetable soybean is famous for its better eating quality and taste, which is usually harvested at fresh pod stage. However, no report is available on nutritional values between vegetable soybean seed at fresh pod stage and mature stage. To better understand the seed nutritional quality differences between fresh pod stage and mature stage in vegetable soybean, five vegetable soybean genotypes were examined. The results found that seeds from fresh edible stage had higher total free amino acid, and higher K, Na, Mn and Zn concentrations. The concentrations of soluble sugar, crude oil as well as unsaturated fatty acid were also higher at fresh pod stage. While total isoflavone, Mg and Fe concentrations were generally higher at full maturity stage. No differences in protein concentration were found between the two stages. Significant genotypic differences were found among nutritional parameters. The genotype Line 61 had the highest total soy isoflavone of 4593 μg g-1, whereas the genotype “Heidou” had the lowest total soy isoflavone of 1700 μg g-1 at mature stage. Correlation analysis indicated that total free amino acid was significantly positively correlated with soluble sugar, crude oil and total isoflavone. Therefore, the nutritional values at fresh pod stage and mature stage differed from the perspective of nutritional compositions. The findings reported here add new knowledge to vegetable soybean function and is a useful starting point for future breeding program and cultivation towards improving the nutritional compositions of soybean species.